2013
DOI: 10.1292/jvms.12-0324
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Sandwich Enzyme-Linked Immunosorbent Assay to Detect and Measure Serum Levels of Canine Ferritin

Abstract: ABSTRACT. We established a homologous sandwich enzyme-linked immunosorbent assay (ELISA) to measure serum levels of canine ferritin. Our assay uses a rabbit anti-canine heart ferritin polyclonal antibody, and canine heart ferritin as a standard. Serum ferritin concentration in healthy dogs (n=163) was 789 ± 284 ng/ml (mean ± standard deviation), a value higher than reported previously. Confidence levels relating to repeatability, dilution and recovery for this method were high. Therefore, we believe our develo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
9
0

Year Published

2013
2013
2015
2015

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 15 publications
(11 reference statements)
0
9
0
Order By: Relevance
“…The iron standard solution (100.5 mg/ l ) used for atomic absorption spectrometry was of chemical analysis grade and was obtained from Kanto Chemical (Tokyo, Japan). Serum ferritin concentration was measured by sandwich enzyme-linked immunosorbent assay (ELISA) using purified rabbit anti-canine heart ferritin polyclonal antibody, as described in our previous report [1]. TIBC was measured by the 2-nitroso-5-( N -propyl- N -sulfopropylamino)-phenol (nitroso-PSAP) method at SRL Inc. (Tokyo, Japan).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The iron standard solution (100.5 mg/ l ) used for atomic absorption spectrometry was of chemical analysis grade and was obtained from Kanto Chemical (Tokyo, Japan). Serum ferritin concentration was measured by sandwich enzyme-linked immunosorbent assay (ELISA) using purified rabbit anti-canine heart ferritin polyclonal antibody, as described in our previous report [1]. TIBC was measured by the 2-nitroso-5-( N -propyl- N -sulfopropylamino)-phenol (nitroso-PSAP) method at SRL Inc. (Tokyo, Japan).…”
mentioning
confidence: 99%
“…Ferritin immunoprecipitation was performed by adding 5 µl (containing 7 µ g of antibody) of purified rabbit anti-canine heart ferritin polyclonal antibody, which was used same antibody in ELISA [1], to 300 µl of canine serum. After incubation overnight at 4°C, ferritin absorbed in the serum supernatant was collected by centrifugation at 9,300 × g for 10 min, and the supernatant then measured as serum.…”
mentioning
confidence: 99%
“…Therefore, it is hoped that a useful method of serologic testing in veterinary medicine is carried out. In a prior study, we used sandwich ELISA [7] testing to measure serum ferritin concentration in a large sample of clinical cases, and we found that splenic HSA frequently caused hyperferritinemia.…”
mentioning
confidence: 99%
“…The other blood sample was anti-coagulated with heparin and centrifuged again for 5 min at 1,640 × g to separate plasma for immediate plasma alanine transaminase (ALT) activity testing using an auto analyzer (AU400; Beckman Coulter, Brea, CA, U.S.A.). Serum ferritin concentration was measured by sandwich enzyme-linked immunosorbent assay (ELISA) using the method described in our previous report [7]. All results are given as mean ± standard deviation (SD).…”
mentioning
confidence: 99%
See 1 more Smart Citation